Ketimpangan Distribusi Pendapatan di Yogyakarta: Analisis Gini Ratio dalam Perspektif Ekonomi Islam - Dita Tasya Ramadhanty; Cintya Aura Paramita; Budi Jaya Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Income inequality remains a persistent issue in economic development in the Special Region of Yogyakarta (DIY), despite the region's relatively strong economic growth. This study aims to examine the level of income inequality using the Gini Ratio as an indicator, investigate its relationship with the development of district/city minimum wages (UMK) and Gross Regional Domestic Product (GRDP) growth, and analyze it from the perspective of Islamic economics. Employing a quantitative descriptive approach and secondary data obtained from the Statistics Indonesia of Yogyakarta (BPS DIY) for the period 2021–2025, the analysis was conducted through the presentation of tables, graphs, and interpretations based on income distribution theory and Islamic economic principles. The findings indicate that the Gini Ratio in DIY remained within the medium-to-high inequality category throughout the observation period, although it showed a declining trend toward the end of the period. Meanwhile, increases in UMK and GRDP growth have not significantly reduced income inequality. From the perspective of Islamic economics, this condition suggests that the principles of distributive justice (al-'adl), balance (tawazun), and welfare (falah) have not been fully achieved. Therefore, more inclusive development policies and the strengthening of Islamic economic distribution instruments are needed to promote a more equitable distribution of welfare among society.